Analisis Pengaruh Tata Kelola Perusahaan Terhadap Manajemen Laba - Yuiyanti, Wiwi; Hariyanti, Anies Indah (Fakultas Ekonomi - Universitas Setia Budi, 2023)
This study aims to analyze the effect of Corporate Governance on earning management. The population in this study was 27 state-owned companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021. The sample technique used was purposive sampling and resulted in 24 companies being selected as samples with a total of 72 observations. The data analysis technique used was multiple regression analysis, as well as hypothesis testing using the Eviews 12 application.The results showed that the audit committee, independent commissioner, institutional ownership and foreign ownership together have a significant effect on earning management, the audit committee and institutional ownership have a significant effect on earning management. Independent commissioners and foreign ownership have no significant effect on earning management.